2007
DOI: 10.2116/analscix.23.x61
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of N,N'-Bis(3-nitrobenzylidene)butane-1,4-diamine

Abstract: Schiff-bases are well-know chelating ligands in coordination chemistry. 1 During the last decade, Schiff-base complexes have been applied to catalytic reactions and biological systems. 2 Schiff bases can be used to obtain optical materials and conducting polymers. 3,4 Thus, new optical and organic conducting materials can be produced by using these compounds. These compounds, containing Schiff bases, seem to be suitable candidates for further chemical modifications, and may be used to produce optical communica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 8 publications
2
4
0
Order By: Relevance
“…1.4440 (7) N ( All the bond lengths and bond angles in the title compound are within normal ranges and comparable to those in the similar compounds 13,14,19 . The C7-N1 bond length of 1.268(8) Å, the C10-N2 bond length of 1.259(8) Å, the C23-N3 bond length of 1.280(8) Å and the C26-N4 bond length of 1.263(7) Å conform to the value for a double bond, while the C8-N1 bond length of 1.468(7) Å, the C9-N2 bond length of 1.440(7) Å, the C24-N3 bond length of 1.459(8) Å and the C25-N4 bond length of 1.459(8) Å conform to the value for a single bond.…”
Section: Table-1 Selected Bond Lengths (å) and Bond Angles (º) Bondsupporting
confidence: 67%
See 1 more Smart Citation
“…1.4440 (7) N ( All the bond lengths and bond angles in the title compound are within normal ranges and comparable to those in the similar compounds 13,14,19 . The C7-N1 bond length of 1.268(8) Å, the C10-N2 bond length of 1.259(8) Å, the C23-N3 bond length of 1.280(8) Å and the C26-N4 bond length of 1.263(7) Å conform to the value for a double bond, while the C8-N1 bond length of 1.468(7) Å, the C9-N2 bond length of 1.440(7) Å, the C24-N3 bond length of 1.459(8) Å and the C25-N4 bond length of 1.459(8) Å conform to the value for a single bond.…”
Section: Table-1 Selected Bond Lengths (å) and Bond Angles (º) Bondsupporting
confidence: 67%
“…The C7-N1 bond length of 1.268(8) Å, the C10-N2 bond length of 1.259(8) Å, the C23-N3 bond length of 1.280(8) Å and the C26-N4 bond length of 1.263(7) Å conform to the value for a double bond, while the C8-N1 bond length of 1.468(7) Å, the C9-N2 bond length of 1.440(7) Å, the C24-N3 bond length of 1.459(8) Å and the C25-N4 bond length of 1.459(8) Å conform to the value for a single bond. The C=N bond lengths are close to the corresponding bond length in N,N'-bis(3-nitrobenzylidene)butane-1,4-diamine [1.267(3) Å] 19 . The molecules are linked through C-H···Cl hydrogen bonds interactions ( Fig.…”
Section: Table-1 Selected Bond Lengths (å) and Bond Angles (º) Bondsupporting
confidence: 54%
“…Diaryl Methylene Diimines. Reaction of 2 equiv of aforesaid aromatic aldehydes with 1 equiv of 1,3-propyl/1,4-butyl/1,2cyclohexyl diamines separately in methanol resulted in diaryl methylene diimines (16)(17)(18)(19)(20)(21)(22)(23) in excellent yields (Figure 2), which were characterized using spectral techniques.…”
Section: Resultsmentioning
confidence: 99%
“…Compound 12 showed maximum ammonium-N retention with value 104 mg/ kg and significantly superior to others as evidenced from DMRT values. The next in performance were compounds 13,3,17,5,22,18,21,16,20 with 67-93 mg/kg ammonium-N. The rest of the compounds lay in the range of 24-64 mg/kg ammonium-N. From the overall performance it was found that the diimines (16)(17)(18)(19)(20)(21)(22)(23) showed moderate ammonium-N content (64-70 mg/kg) while monoimines showed low to high ammonium-N content (24-104 mg/kg).…”
Section: Resultsmentioning
confidence: 99%
“…[6][7][8][9] In the present work, we report on the crystal structure of another diimine Schiff base, viz. N,N′-bis(trans-cinnamaldehyde)ethylenediimine (ca2en) (Fig.…”
Section: 5mentioning
confidence: 99%